How does the Production of Unconventional Resources of Energy Influence Energy Security: Empirical Approach - Obadi, Saleh Mothana; Gardonova, Kristina (International Journal of Energy Economics and Policy, 2019)
This paper examines the issue of production of unconventional resources of energy and their impact on energy security. Energy security is influenced by several factors, among them the endowment of natural energy resources, either conventional or unconventional, and the level of their production. A VAR model has been constructed to examine the influence of tight oil production on the price of oil and on other variables, moreover, which variables influence the price of oil most. These findings may be interpreted by generalization as influencing the energy security and by extrapolation the results hold same for the American market than for the rest of the world, as the US largely dictates the price of oil worldwide. Our results inter alia suggest that, unconventional oil Granger causes the price of WTI, and the opposite in not true. We found also that there is a slightly positive correlation between the stocks and tight oil and stocks and oil exports, hence we can conclude that a higher production leads to higher amount of oil stocked and exported. What is more interesting is that tight oil reports greater correlation than conventional oil production. Keywords: Granger Causality, Oil Price, Energy Security, Unconventional Resources JEL Classifications: Q32, Q41, Q43 DOI: https://doi.org/10.32479/ijeep.7878